Characterization of a new Leishmania major strain for use in a controlled human infection model - Ashwin, Helen; Sadlova, Jovana; Vojtkova, Barbora; Becvar, Tomas; Lypaczewski, Patrick; Schwartz, Eli; Greensted, Elizabeth; Van Bocxlaer, Katrien; Pasin, Marion; Lipinski, Kai S; Parkash, Vivak; Matlashewski, Greg; et al. (Nature communications, 2021)
Leishmaniasis is widely regarded as a vaccine-preventable disease, but the costs required to reach pivotal Phase 3 studies and uncertainty about which candidate vaccines should be progressed into human studies significantly limits progress in vaccine development for this neglected tropical disease. Controlled human infection models (CHIMs) provide a pathway for accelerating vaccine development and to more fully understand disease pathogenesis and correlates of protection. Here, we describe the isolation, characterization and GMP manufacture of a new clinical strain of Leishmania major. Two fresh strains of L. major from Israel were initially compared by genome sequencing, in vivo infectivity and drug sensitivity in mice, and development and transmission competence in sand flies, allowing one to be selected for GMP production. This study addresses a major roadblock in the development of vaccines for leishmaniasis, providing a key resource for CHIM studies of sand fly transmitted cutaneous leishmaniasis.
Keywords: sekvenování celého genomu; Psychodidae; modely nemocí na zvířatech; Izrael; fylogeneze; Phylogeny; myši inbrední BALB C; paraziti; Leishmaniasis, Cutaneous; hmyz - vektory; Mice, Inbred BALB C; Animals; Israel; lidé; Leishmania major; Humans; zvířata; leishmanióza kožní; Disease Models, Animal; myši; Insect Vectors; Parasites; Mice; Whole Genome Sequencing